Analysis of Yarn Materials Defects in the Warping Process using Fault Tree Analysis with Improvement Proposals 5W1H Based on the 5W1H Method - Rafida, Halimas Nafi; Rochmoeljati, Rochmoeljati (Newinera Publisher, 2025)
Quality control is a critical aspect of the textile industry, essential for maintaining product consistency. However, defects in yarn materials continue to persist, particularly during the warping process. This study investigates yarn defects at PT X using the Fault Tree Analysis (FTA) method, identifying 15 root causes and proposing corrective measures based on the 5W1H approach. The research specifically addresses defects in Tetoron Rayon (TR) yarn Ne 30, with a focus on Cross Defects, Defective Rolls, and Nglokor Rolls. The FTA method offers a structured approach to failure analysis, while the 5W1H method is employed to derive strategic corrective actions. The findings demonstrate that the probability of defect occurrence varies between the Direct and Sectional Warping processes. Cross Defects occur with probabilities of 0.1333% and 0.126%, Defective Rolls with probabilities of 0.159% and 0.243%, and Nglokor Rolls with probabilities of 1% and 0.171%, respectively. The analysis identifies 15 primary root causes contributing to these defects, which include machine-related failures, human error, and material inconsistencies. Based on these findings, the study recommends the implementation of preventive maintenance schedules, operator training programs, and a more rigorous adherence to standard operating procedures (SOPs). The proposed improvements are expected to optimize the warping process and enhance the overall quality of the product.